THE SIGNIFICANCE OF HISTORICAL KNOWLEDGE IN FORMING YOUTH'S WORLD VIEW IN NEW UZBEKISTAN - Kholmatov Mukhsin Moydinovich; Amanov Abdusalim Abdusalomovich (Web of Journals Publishing, 2023)
The article highlights the issues of historical impartiality, which is one of the important factors in the formation of the world view of young people, of educating our young people based on our historical values, and protecting them from various influences. Also, attention is paid to a number of problems that require clarification in front of the science of history.
Keywords: historical objectivity, democratic reforms, historical value, foreign ideas, institute of history.